2004
DOI: 10.57054/jhea.v2i3.1667
|View full text |Cite
|
Sign up to set email alerts
|

5 - Higher Education in Ethiopia: The Vision and Its Challenges

Abstract: Ethiopia is embarked on a higher education expansion and reform programme of impressive dimensions. Expansion will create new universities, establish three sys- tem support agencies, mount new courses, and triple enrolments. Reforms intro- duce increased institutional autonomy, curriculum revisions, new funding arrange- ments and student contributions by means of a graduate tax. This article analyses current higher education reform efforts in Ethiopia. It begins by sketching the so- cial context in which highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 2 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…The questionnaire and checklist were taken from the revised and analyzed literature to gather safety practices. 14 We then distributed the created questionnaires to instructors, department heads, and technical assistants to collect quantitative data. Observational checklists were used to collect qualitative information and were finally integrated and triangulated to enrich and elaborate on quantitative data collected through questionnaires.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The questionnaire and checklist were taken from the revised and analyzed literature to gather safety practices. 14 We then distributed the created questionnaires to instructors, department heads, and technical assistants to collect quantitative data. Observational checklists were used to collect qualitative information and were finally integrated and triangulated to enrich and elaborate on quantitative data collected through questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Out of 17 participants, 58.8% (10) were from the department of the medical laboratory, and 41.2% (7) were from the environmental health department. Regarding the sex of respondents, 82.4% (14) were females, while 17.6% (3) were males.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1992 Mwira and Hughes reported that both the student allowances and the student loans scheme had been earmarked for change and that plans had been made to reduce costs by admitting more day students, streamlining the operation of housing and dining facilities, and also abolishing allowances. According to William Saint (2004), Ethiopia is currently expanding its higher education system and is looking at new ways of funding it, including introducing a graduate tax, and, as Johnstone (2003) reports, a loan scheme modelled after the Australian income-contingent loan scheme is also being considered. In other countries like Uganda, Zimbabwe, Rwanda, and Kenya, universities have responded to the challenges of financing by offering parallel systems for fee-paying students, where some university spaces are set aside for students who are able to pay for their education.…”
Section: S T U D E N T F I N a N C I N G P O L I C I E S I N A F R I C Amentioning
confidence: 99%